Inhibitors of HIV-1 maturation: Development of structure–activity relationship for C-28 amides based on C-3 benzoic acid-modified triterpenoids. Issue 8 (15th April 2016) - Swidorski, Jacob J.; Liu, Zheng; Sit, Sing-Yuen; Chen, Jie; Chen, Yan; Sin, Ny; Venables, Brian L.; Parker, Dawn D.; Nowicka-Sans, Beata; Terry, Brian J.; Protack, Tricia; Rahematpura, Sandhya; et al.
Graphical abstract: Abstract: We have recently reported on the discovery of a C-3 benzoic acid (1 ) as a suitable replacement for the dimethyl succinate side chain of bevirimat (2 ), an HIV-1 maturation inhibitor that reached Phase II clinical trials before being discontinued. Recent SAR studies aimed at improving the antiviral properties of2 have shown that the benzoic acid moiety conferred topographical constraint to the pharmacophore and was associated with a lower shift in potency in the presence of human serum albumin. In this manuscript, we describe efforts to improve the polymorphic coverage of the C-3 benzoic acid chemotype through modifications at the C-28 position of the triterpenoid core. The dimethylaminoethyl amides17 and23 delivered improved potency toward bevirimat-resistant viruses while increasing C24 in rat oral PK studies.